Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The use of special education teachers in Makkah Al-Mukarramah for electronic educational games as an educational medium and the obstacles to their use Mrs. Waed Juma Rashid Al-Subhi, Co-Prof. Abdullah Musharraf Alshaaeir 2. Design E-learning Environment Based on Learning Platforms and its impact on Achievement and Developing Digital Citizenship Skills in the Computer course for Middle school students Mrs. Manal Rabeh Alhejaili 3. The Level of Achieving Intermediate Stage Curricula the National-Transformation Program 2020 Goals from the point of view of teachers in the schools of the West Riyadh Office for Boys Mr. Bandar Mohammd Alsomaie , Co-Prof. Ahmed Hasan Albdour 4. The Effect of Creating 3D Software Using (CoSpaces Edu) To Develop Coding Skills for Primary School Students Mrs. Areej Abdullah Alghamdi , Mrs. Layla Hamad Harboush , Co-Prof. Amjaad Tariq Mujallid 5. The impact of teaching by the guided imagination strategy on developing creative expression skills for high school students in Republic of Yemen Dr. Bushra Muhammad Yahya Rafiq Allah 6. Designing and testing a module based on the integrated approach between the subjects of geography and natural sciences. A case study of the common core science stream in the Moroccan high school Prof. Abdelali Soulali 7. The Role of Social Upbringing Institutions in Raising Awareness and Counseling about the Danger of Drugs, Khartoum, Sudan Dr. Shaza Omer Ali The Level of Conceptual Understanding of Functions and their Transformations and its Relationship with the Productive Motivation among Mathematics Students in the Faculty of Education University of Sana`a Instructor Abdol-Rahman Ali Saleh Al-Mahab , Prof. Radman Mohamed Saeed